Bariatric Surgery in Rats Upregulates FSP27 Expression in Fat Tissue to Affect Fat Hydrolysis and Metabolism. (8th May 2019) - Hu, Jingyao; Wang, Mofei; Zhou, Yong; Zhang, Xiaowei; He, Bing; Liu, Lei; Ma, Rui; Zhang, Tianyi; Liu, Keyi; Wang, Yong; Liu, Jingang
Abstract : Purpose . To explore the changes in FSP27 expression and fat metabolism in adipose tissue and their relationship after bariatric surgery in rats. Method . Food intake, body weight, triglyceride content, fat distribution, and fat cell morphology were evaluated in rats grouped into control, sham, sleeve gastrectomy (SG), and Roux-en-Y gastric bypass (RYGB) groups. Immunohistochemistry and western blotting were used to detect protein expression and real-time PCR was used to detect mRNA expression. Mouse 3T3-L1 preadipocytes were used to assess the effects of different energy levels and nutrient factors on FSP27 in adipocytes. Result . Food intake, body weight, and triglyceride levels were reduced in RYGB and SG rats within 28 days after surgery, with a more pronounced effect in the RYGB group. Weight loss was mainly due to loss of fat mass rather than loss of lean mass, with the most pronounced decrease in trunk fat. FSP27 expression increased in lean rat adipocytes accompanied by increased lipid droplets (LDs). In SG and RYGB rats, the FSP27 protein concentration gradually increased in white adipose tissue (WAT) after operation. Hormone-sensitive lipase (HSL), p-HSL/HSL, Adipose Triglyceride Lipase (ATGL), and Comparative Gene Identification-58 (CGI-58) gradually decreased in SG and RYGB rats, but they were always higher than in control and sham animals. FSP27 was also decreased in 3T3-L1 adipocytes of animals with a high-energy diet. Conclusion . FSP27 is associated with rat lipid metabolism and its expression varies with energy and nutrient supply. It can inhibit excessive hydrolysis and fat accumulation by regulating HSL and ATGL expression and by mediating LDs formation.